2018
DOI: 10.1093/rheumatology/key213
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous cyclophosphamidevsrituximab for the treatment of early diffuse scleroderma lung disease: open label, randomized, controlled trial

Abstract: Clinical Trials Registry - India, www.ctri.nic.in, CTRI/2017/07/009152.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
0
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(157 citation statements)
references
References 25 publications
3
135
0
19
Order By: Relevance
“…Consistent with previous reports, Th2 cell numbers were greatly increased in bullous pemphigoid tissues and outnumbered those in SSc and healthy control skin ( Figure 2C and Supplemental Figure 2). Despite the 5-to 10-fold greater number of CD4 + T cells in skin biopsies of bullous pemphigoid patients compared with SSc biopsies, we found the absolute numbers of tissue-infiltrating T lymphocytes have not been systematically interrogated at the tissue level (22)(23)(24).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Consistent with previous reports, Th2 cell numbers were greatly increased in bullous pemphigoid tissues and outnumbered those in SSc and healthy control skin ( Figure 2C and Supplemental Figure 2). Despite the 5-to 10-fold greater number of CD4 + T cells in skin biopsies of bullous pemphigoid patients compared with SSc biopsies, we found the absolute numbers of tissue-infiltrating T lymphocytes have not been systematically interrogated at the tissue level (22)(23)(24).…”
Section: Resultsmentioning
confidence: 59%
“…Although prominent numbers of both B and T cells were observed, the absolute number of infiltrating T cells was greater than those of infiltrating B cells ( Figure 1, A and B). Although randomized double-blind clinical trials examining the utility of B cell depletion therapy in SSc have not been performed, some studies have reported clinical improvement with rituximab, especially in the context of early diffuse SSc (22,23). Additionally, activated B cells have been observed in the circulation of SSc patients (24,36).…”
Section: Resultsmentioning
confidence: 99%
“…Recent data from a Phase 3 trial showed that the treatment of early ILD (mean FVC% of 82% with mild ILD on HRCT) in high‐risk populations (early diffuse cutaneous SSc and elevated C‐reactive protein [CRP] with 50% having positive anti‐SCL‐70 antibodies) with tocilizumab led to stabilization of FVC% vs a decline of 6.5% in the placebo group at 48 weeks . Similarly, an open‐label trial of patients with early diffuse cutaneous SSc and positive anti‐SCL‐70 found improvement in FVC% at 24 weeks with the use of two courses of rituximab (1000 mg × 2 doses) vs monthly pulse CYC . We offer treatment to patients with subclinical ILD and elevated CRP and/or positive anti‐SCL‐70.…”
Section: Treatmentmentioning
confidence: 92%
“…However, MMF is now the most widely used therapy for SSc-ILD and has been endorsed as firstline therapy by consensus panels of experts [46,53,54]. Rituximab and azathioprine are also used in the treatment of SSc-ILD, but the evidence that these drugs may preserve or improve lung function in these patients comes solely from retrospective or open-label studies [55][56][57][58].…”
Section: Treatment Of Autoimmune Ildsmentioning
confidence: 99%